Promoting quality of life for the elderly through digital inclusion: EnvelheSer Project (Research, Society and Development, 2023)
The proportion of people over 60 years old in the world will increase to 1 in every 6 people by 2050, while life expectancy has increased to 90% in countries with higher life expectancy. The COVID-19 pandemic has revealed the urgency of issues related to longevity. During social isolation, digital technologies have become great allies of the elderly population, helping to minimize the loneliness of the elderly and providing them with more attention and care. The aging phase presents unique challenges for the elderly, such as the possibility of a lonely life, loss of loved ones, and lack of support network, which can make them vulnerable. Technology can be a tool for help, but many elderly people have difficulties in understanding and using these technologies, which can lead to inequality and isolation. The lack of skill and access to technology can also limit their ability to stay in touch with society independently. Thus, this work aims to analyze and discuss some aspects of the application of the EnvelheSer project, a project that aims to provide digital inclusion to the elderly. In this way, it was seen that the elderly need more opportunities and that projects like this need to be progressively more present in society.